2017
DOI: 10.1111/1346-8138.13791
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum MFG‐E8 level is possibly associated with the presence of high‐intensity cerebral lesions on magnetic resonance imaging in patients with systemic lupus erythematosus

Abstract: Human milk fat globule-EGF factor 8 (MFG-E8), also known as lactadherin, is a secreted glycoprotein that plays essential roles in the clearance of apoptotic cells and angiogenesis. It has been reported that serum MFG-E8 levels are higher in systemic lupus erythematosus (SLE) patients compared with in healthy controls; however, a previous study reported no correlation between serum MFG-E8 levels and SLE disease activity. The objective of this study was to assess serum MFG-E8 levels and their clinical associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, the expression level of MFGE8 is a very important factor in its function, and can be said to be related to the pathogenesis of autoimmune diseases including SLE. In addition, serum MFGE8 levels in Japanese patients with SLE were significantly higher than those in healthy individuals 23,28 . Moreover, the medical treatment of SLE resulted in significantly lower levels of MFGE8.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the expression level of MFGE8 is a very important factor in its function, and can be said to be related to the pathogenesis of autoimmune diseases including SLE. In addition, serum MFGE8 levels in Japanese patients with SLE were significantly higher than those in healthy individuals 23,28 . Moreover, the medical treatment of SLE resulted in significantly lower levels of MFGE8.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that MFG‐E8 is implicated in the pathogenesis of autoimmune disorders, such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). The serum MFG‐E8 level in SLE patients was higher than that in healthy individuals , and aged MFG‐E8–knockout (KO) mice developed glomerulonephritis and showed antinuclear antibody (ANA) production . Serum MFG‐E8 levels in RA patients and arthritic mice were significantly lower than those in healthy controls, and MFG‐E8–KO mice exhibited exacerbated arthritis .…”
Section: Introductionmentioning
confidence: 99%
“…While PS is normally located on the plasma membrane inner leaflet during viral budding the PS becomes exposed on the HIV-1 envelope potentially serving as a target for MFG-E8 and related PS binding proteins (Morizono and Chen, 2014; Wu and Shroff, 2018). Because MFG-E8 is widely expressed and found at substantial concentrations in blood and potentially the lymph (Kishi et al, 2017; Yamaguchi et al, 2008); most HIV-1 virions likely bear MFG-E8. This would target HIV-1 virions to monocytes and macrophages that express αvβ3/5 integrins.…”
Section: Introductionmentioning
confidence: 99%